MAPPING THE KOREAN WAVE STUDIES IN THE PERSPECTIVE OF COMMUNICATION SOCIOLOGY: A BIBLIOMETRIC ANALYSIS - Dayinta Erasmarta; Filosa Gita Sukmono (Jurnal Lectura, 2026)
The phenomenon of the Korean Wave (Hallyu) has evolved from a regional entertainment trend into a complex global force influencing digital culture and social interactions. While previous studies have predominantly focused on the economic and tourism impacts of Hallyu, a comprehensive mapping of its sociological dimensions remains limited. This study aims to map the development trends, conceptual structures, and evolution of Korean Wave research within the perspective of the sociology of communication. Using a bibliometric analysis approach, this study analyzed 209 scientific documents published between 2015 and 2026 retrieved from the Scopus database. The data were processed using R-Package Biblioshiny to generate performance analysis and science mapping. The results indicate a significant surge in scientific production starting in 2019, driven by the global expansion of K-Pop fandoms. The network analysis reveals a distinct polarization in the research landscape: one cluster focuses on "social media activism and participatory culture," while another emphasizes the "psychological well-being of fans," particularly among adolescents and female audiences. Furthermore, the thematic evolution analysis highlights a paradigm shift from content-based studies (drama/TV) to human-centric inquiries (identity, gender, and mental health). This study concludes that the scholarship on the Korean Wave has matured into a critical sociological discourse, moving beyond mere consumption to explore how digital platforms facilitate identity negotiation and transnational community formation.